2014
DOI: 10.4143/crt.2014.009
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment Modalities, Prognostic Predictors and Outcomes of Uterine Carcinosarcomas

Abstract: PurposeThe purpose of this study is to evaluate the clinicopathological characteristics, treatment, and prognosis of uterine carcinosarcoma (UC).Materials and MethodsA retrospective review of three cancer registry databases in Turkey was conducted for identification of patients diagnosed with UC between January 1, 1996, and December 31, 2012. We collected clinicopathological data in order to evaluate factors important in disease- free survival (DFS) and overall survival (OS).ResultsA total of 66 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…In the present study, we observed that adjuvant RT with CT was predictive of better survival in UCS patients compared with individuals receiving CT or RT alone. Gungorduk et al [ 24 ] conducted a retrospective review of three cancer centers involving 66 UCS patients, noting that adjuvant CT with RT is associated with improved OS compared with CT or RT alone (HR, 3.3; 95% CI, 0.7 to 15.0; p=0.01), consistent with the results of the present study. We collected a larger number of cases and prospective trials warranting the evaluation of the effectiveness of multimodal therapy in UCS patients.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we observed that adjuvant RT with CT was predictive of better survival in UCS patients compared with individuals receiving CT or RT alone. Gungorduk et al [ 24 ] conducted a retrospective review of three cancer centers involving 66 UCS patients, noting that adjuvant CT with RT is associated with improved OS compared with CT or RT alone (HR, 3.3; 95% CI, 0.7 to 15.0; p=0.01), consistent with the results of the present study. We collected a larger number of cases and prospective trials warranting the evaluation of the effectiveness of multimodal therapy in UCS patients.…”
Section: Discussionsupporting
confidence: 89%
“…92.9% of the women in our study were postmenopausal, but none had a history of previous pelvic irradiation or tamoxifen use. Previously reported mean of age at diagnosis is 62 years [9], which is in line with our results (69.2 years).…”
Section: Discussionsupporting
confidence: 93%
“…For late-stage disease, cytoreductive surgery has shown to increase OS [3,7]. Concerning adjuvant therapy, there is ongoing discussion whether it improves survival and until now no evidence-based treatment strategy is established [8,9]. This retrospective study evaluates the clinical presentation, treatment and survival of Caucasian patients diagnosed with UCS in the Comprehensive Cancer Network south region in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…The term carcinosarcoma was first used by Virchow in 1864 2. Carcinosarcomas can occur in diverse organs, such as the skin, lungs, esophagus, colon, and uterus 3456. Dawson7 is credited with describing the first cutaneous carcinosarcoma in 1972.…”
Section: Introductionmentioning
confidence: 99%